Working memory span and ADHD symptoms - Helga Bjarkadóttir 1989- (2014)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder that has been linked to impairments in working memory, both in theory and empirically. The primary aim was to investigate the relation of ADHD symptoms and working memory in healthy adults. More recently, research have pointed to inattentive symptoms as being most associated with impaired performance on neuropsychological tests. Therefore, the secondary aim was to determine if working memory would be more related to inattentive symptoms than to hyperactive-impulsive symptoms. Thirty-seven students in Reykjavík University (28 women and 9 men) participated in this study, aged 20 to 30 years. ADHD symptoms were assessed with an 18-item self-report questionnaire of statements related to symptoms of ADHD. The working memory task used was a modified version of the operation span task. Results showed a significant correlation between working memory and inattentive symptoms but not for the hyperactive-impulsive symptoms. No significant differences in working memory based on groups with low, medium, and high symptoms were found. Because of the small sample size, no clear conclusion could be drawn from these findings and need to be viewed as preliminary. Future research should look more closely at possible working memory differences between the ADHD subtypes, using larger samples. Keywords: ADHD, subtypes, working memory, adult, operation span task